The Catalytic Function of Nonheme Iron (III) Complex for Hydrocarbon Oxidation - Giorgos Bilis; Maria Louloudi (Bioinorganic Chemistry and Applications, 2010)
A detailed catalytic study of LFeIIICl (where L=3-{2-[2-(3-hydroxy-1,3-diphenyl-allylideneamino)-ethylamino]-ethylimino}-1,3-diphenyl-propen-1-ol) for hydrocarbon oxidation was carried out, focusing on the role of solvent, atmospheric dioxygen, and oxidant on catalytic efficiency. The data showed that LFeIIICl catalyst was efficient in homogeneous hydrocarbon oxidations providing significant yields. Moreover, tert-BuOOH provided comparable oxidation yields with H2O2, slightly favoring the formation of alcohols and ketones versus epoxides. Dioxygen intervened in the catalytic reaction, influencing the nature of oxidation products. The polarity of solvent strongly influenced the reaction rates and the nature of oxidation products. A mechanistic model is postulated assuming that LFeIIICl functions via the formation of iron-hydroperoxo-species, followed by a radical-based mechanistic path.